PERFORMING ARTS AS A TOOL FOR COMMUNITY HEALTH AND SOCIAL INCLUSION - Raje, Vaishali V; Punitha VC; Shanthi P; Arivukkodi R; Kodi K, Malar; Parimala K; T. Puhazhendhi (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The use of performing art has also gained recognition as a great tool to promote health among the community, social inclusion and culture. The paper will examine the significance of performing arts including theatre, music, dance, and participatory performance in enhancing the emotional state and transforming communities into social entities. Unlike the conventional health promotion techniques that have relied on informational campaigns to a larger extent, performing arts provide interactive and participative stages that can enable creativity, communication and collective action. Through the activities, the individuals are able to communicate and share, give each other their experiences, and have worthwhile relationships that lead to enhanced state of mental health and neighborhood integration. The article gives a well-developed literature review of other works available on arts-based interventions and their impact on the social inclusion and health of the population. A number of performing arts strategies such as theatre-based sensitisation, community music, dance and movement therapy and participatory performances are discussed with an aim of understanding their contribution to emotional wellbeing, cultural participation, and social empowerment. The comparative analysis of these interventions demonstrates the advantages of these interventions, the degree of community involvement, and the potential constraint in the real world setting. Based on such findings, the study provides a conceptual framework on the manner in which performing arts can become part of the community health strategies. The proposed model emphasizes on the creative interaction, community engagement, active participation and remedial evaluation in such a way that the arts based programs can be successfully implemented and sustainable in the long run. The research also presents the possibilities of the likely increase in the mental health along with the social cohesion and the cultural identity as well as the issues with the availability, resources and impact assessment are also discussed.